A combination of metabolite profiling and network pharmacology to explore the potential pharmacological changes of secoisolariciresinol-diglycoside. Issue 57 (21st September 2020) - Zhang, Fengxiang; Cui, ShuangShuang; Li, Ziting; Yuan, Yulinlan; Li, Chang; Li, Ruiman
Abstract : The prototypes and metabolites formed from the use of traditional Chinese medicines (TCM) are typically the cause of both side side-effects and therapeutic results. Abstract : The prototypes and metabolites formed from the use of traditional Chinese medicines (TCM) are typically the cause of both side side-effects and therapeutic results. Therefore, the characterization of in vivo substances and the determination of functional changes are of great importance for clinical applications. Secoisolariciresinol-diglycoside (SDG), one major compound in flaxseeds, was used as a potential drug to treat tumors in the clinic; however, the metabolism information and functional changes of SDG in vivo were limited, which limited its application. In this study, an integrated strategy based on metabolite profiling and network pharmacology was applied to explore the metabolism feature and functional changes of SDG. As a result, a total of 28 metabolites were found in rats, including 14 in plasma, 22 in urine, 20 in feces, 7 in the heart, 14 in the liver, 8 in the spleen, 10 in the lungs, 14 in the kidneys, and 4 in the brain. Among them, M8, M13 and M26 were the main metabolites of SDG in rats and 24 were characterized for the first time. The metabolic reactions contained phase I reactions of demethylation, dehydroxylation, deglycosylation, arabinosylation and glycosylation, and phase II reactions of glucuronidation and sulfation were also observed. Notably, the arabinosylation and glycosylation were found in SDG for the first time. Meanwhile, 121 targets of SDG and its metabolites were found, PRKCB was the main target of SDG, and the metabolites of SDG mainly targeted HSP90A1, IL6, AKT1, MAPK3, MTOR, PIK3CA, SRC, ESR1, AR, PIK3CB, and PIK3CB. The difference of targets between SDG and its metabolites could result in its additional functional pathways of neurotrophin signaling pathway, PI3K-Akt signaling pathway, HIF-1 signaling pathway or indications of anti-prostate cancer. This work provided a new insight for exploring the mechanism and therapy indications of drugs.